FEMINIST RESISTANCE AND SUFFERING OF PROTAGONIST IN EDNA O'BRIEN NOVELS (International Journal of Food and Nutritional Sciences, 2023)
Edna O'Brien's The Country Girls Trilogy explores the personal struggles of women in conservative rural Ireland. The protagonists, Kate and Baba, experience profound emotional and psychological suffering due to societal constraints, particularly rooted in the strict Catholic environment. Their journey is one of resistance against these societal norms as they seek independence and personal freedom. This paper delves into how both characters navigate their desires, endure suffering, and exhibit forms of resistance, thereby reflecting thelarger theme of female empowerment amidst patriarchal oppression.